SETTLEMENT OF PROBLEM FINANCING AFTER THE COVID-19 PANDEMIC AT BANK SYARIAH INDONESIA, BANDA ACEH - Rangkuti, Astriyanthi (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2023)
This research examines the Analysis of Troubled Financing Restructuring and the Urgency of Post-Covid-19 Agreement Renewal at BSI Aceh. The purpose of this research is to find out the implementation of post-covid-19 problem financing restructuring at Bank Syariah Indonesia (BSI) Aceh Branch, and to find out the urgency of renewing the post-covid-19 financing contract at BSI Aceh, to find out the Handling of Post-Covid-19 Financing Restructuring at BSI Aceh. This research uses a qualitative method with a descriptive approach. The research took place at BSI Aceh branch. The data sources used in this research are primary data sources and secondary data sources. The data collection methods used are observation, interviews, and documentation. The data analysis technique used in this research is descriptive analytical technique. The results showed that BSI in Aceh in providing financing restructuring to customers due to the Covid-19 Pandemic is based on Financial Services Authority Regulation Number 16/POJK.03/2014, which can only be given to customers who have difficulty fulfilling their obligations to the bank due to their business being affected by Covid-19. The stages of restructuring are rescheduling, re-conditioning and re-structuring. All these stages are carried out in order to fulfil the purpose of the initial contract of a customer with the bank, namely to give birth to a legal effect or mutual intention that is intended and which the parties want to realise through making a contract.